Automated Digital Image Optimisation in Intraoperative 2D and 3D Imaging Using a Mobile C-Arm With Flat-Panel Detector - Groh, Johannes; Perl, Markus; Bräuer, Lars; Stadthalter, Holger (International Journal of Medical Robotics and Computer Assisted Surgery, 2025)
Background: Assistance tools for intraoperative 2D and 3D imaging to decrease acquisition effort and to improve assessment of 3D image data were evaluated. Methods: Two automated optimisation procedures were evaluated in a cadaver (Cios Spin, Siemens, Germany): The ScrewScout function for assisted pedicle screw assessment. Then, an algorithm for metal artefact reduction (MAR). Additionally, a tool for simplified setting of image contrast and brightness was evaluated regarding the result and elapsed time. Results: The time required without automated assistance was 83s [70–105]. With the computer assistance, this time was significantly lower at 22s [15–32] (p = 0.003). MAR resulted in an improvement in image impression. This improvement became smaller with increasing clinical experience. The time needed for setting of image acquisition parameters was significantly (p = 0.05) lowered from 140s [24–389] to 61s [14–166] using the assistance tool. Conclusions: Automated assistance tools for image optimisation can provide practical support in the intraoperative setting.
CRIS-Team Scopus Importer:2025-03-14
Keywords: automated image analysis; intraoperative imaging; MAR; metal artifact reduction; ScrewScout; SpotAdapt

CPR related injuries of the chest wall: direct and indirect fractures - Schenderlein, Anne; Groh, Johannes; Kern, Florian; Perl, Mario; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2025)
BACKGROUND: Rib and sternum fractures are common injuries associated with cardiopulmonary resuscitation (CPR). The fracture mechanism is either direct by application of force on sternum and anterior ribs or indirect by bending through compression of the thorax. The aim of this study was to determine morphologies of rib fractures after CPR and to reevaluate prior findings on fracture localisation, type and degree of dislocation. METHODS: The present study was based on all inpatients treated for chest wall fractures after non traumatic cardiac arrest at a Level 1 Trauma Centre from 2010 to 2016 who had received CT scans. Each fracture was analyzed for location, degree of dislocation and fracture type classified according to AO/OTA and CWIS. We also analysed Fracture Line orientation. RESULTS: We enrolled 40 patients with a total of 423 rib fractures. We found most fractures anterolaterally between the 3rd to 6th rib symmetrically on both sides of the thorax. We found sternum fractures in 30% of the patients, 50% being located at the at the corpus sterni between rib 3 and 4. All patients with sternum fractures suffered from rib fractures and most had fractures of the cartilage or osteochondral junction. All cartilage fractures were straight, undisplaced type A fractures. Most indirect fractures occurred anterolaterally between 50 and 60° in the axial plane. More than 90% of those fractures were classified as type A, 70% showed a straight fracture line and 60% were undisplaced. There was no difference in degree of dislocation between straight and oblique fracture lines. We found 143 incomplete fractures. CONCLUSION: We confirmed prior findings regarding fracture patterns in CPR related injuries. We observed approximately 2-3 times as many straight-lined fractures as oblique ones following indirect trauma. One third of all fractures are incomplete, these highlights the special characteristics like high elasticity of ribs.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Chest wall injury; CPR; Flail chest; Fracture morphology; Indirect fractures; Rib fractures

Do we have to redefine type B-fractures of the rib cartilage? - Groh, Johannes; Kern, Florian; Perl, Mario; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2024)
Objectives: Aim of this work was the evaluation and validation of the AO/OTA classification of the anterior chest wall, here especially for the rib cartilage. Methods: Study design was a retrospective analysis of patients who were hospitalized with fractures of the thoracic wall in the years 2010–2016. This resulted in a collective of n = 124 patients. All fractures of the anterior chest wall were classified according to their location, dislocation and fracture type according to the AO classification. An analysis of possible subtypes was carried out. Results: 29.0% (36) of the patients had fractures of the rib cartilage. 23 of the 36 (64%) patients had multiple fractures, the total number of single fractures amounted to 94. 53.2% (50) of these fractures were in the right hemithorax, 46.8% (44) in the left hemithorax. 95.7% (90) of the fractures were A-fractures, 4.3% (4) were C-fractures. There were no B fractures. The C fractures also consisted exclusively of A fractures (AA fractures). 59.6% (56) of the fractures showed a dislocation. 30.9% (29) were avulsion fractures of either the osteochondral (22.3% (21)) or the sternocostal junction (8.5% (8)). Discussion and conclusion: The costal cartilage obviously does not show typical B fractures as we know them from shaft fractures of long bones. We have compiled a structured analysis in the attached manuscript and validated the classification proposal. In conclusion, we propose an adaptation of the classification proposal based on our data with redefining type B fractures as fractures of the osteochondral joints.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Anterior rib; AO/OTA classification; Costal cartilage; Costochondral; Rib cartilage; Rib fracture; Sternocostal

Innovative 3D-Bildgebung - Groh, Johannes; Schramm, Simon; Renner, Nina; Krause, J.; Perl, Markus (Die Unfallchirurgie, 2023)
Intraoperative 2D fluoroscopy is often performed for repositioning and implant control. However, this does not always provide the details needed to reliably detect joint steps or incorrect repositioning. Over the last few years, intraoperative 3D imaging has been established and further developed. Multiple studies demonstrate an advantage and better intraoperative control through 3D imaging. Examples are the upper ankle, the proximal tibia and the distal radius; the rates of intraoperative revisions with digital volume tomography (DVT) are between 20–30%. Technical advancements, such as metal artifact reductions, automated plane setting, automated screw detection, and robotic DVT devices, facilitate intraoperative operation, shorten surgical time, and provide improved image quality. By processing the data sets in the form of an immersive, computer-simulated image in terms of “augmented reality” (AR), increased precision can be achieved intraoperatively while reducing radiation exposure. The implementation of these systems is associated with costs, which are offset by cost savings from avoided revisions. Adequate counter-financing is still lacking at the present time. Intraoperative 3D imaging represents an important tool for intraoperative control. The current data situation makes it necessary to address the routine use of 3D procedures, especially in the joint area. The indications are becoming increasingly broader. Technical innovations such as robotics and AR have significantly improved 3D devices in recent years and offer high potential for integration into the OR.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Augmented reality; Digital volume tomography; Intraoperative imaging; Joints; Robotics

Intraoperative Navigation einer Distraktionsverletzung der BWS bei schwersten skoliotischen Veränderungen - Schramm, Simon; Groh, Johannes; Krause, Johannes; Perl, Mario (Die Unfallchirurgie, 2024)
The case of a 43-year-old male patient is described, who suffered several injuries due to a traffic accident, including a distraction injury to the thoracic spine. A specific feature of this case was the existing spondylodesis with material fracture and secondary loss of reduction. Due to this, the guidewires of the pedicle screws were placed in a navigation pattern in the absence of adjustable pedicles and an abnormal screw corridor. This guarantees an optimal positioning with associated patient safety.
CRIS-Team Scopus Importer:2024-05-10
Keywords: 3D imaging; Distraction injury; Multiple trauma; Navigation; Spinal trauma

Precision and effort in robot-assisted placement of pedicle screws compared to standard surgical navigation - Sippel, Julia Katharina; Groh, Johannes; Bräuer, Lars; Perl, Mario; Stadthalter, Holger (Scientific Reports, 2024)
Aim was to compare image-guided navigation with a robot-assisted solution for performing MISS regarding precision, required time and subjective aspects. 90 pedicles were instrumented on two torsos, half with navigation, half robot-assisted. Precision analysis between both solutions didn’t show a significant difference. Time measurement showed a significantly longer duration per wire for the robot-arm on the first torso and a not significant longer duration on the second torso, where a significant reduction in the mean duration was shown. There was no significant difference in the subjective impressions comparing navigation and robot except the possibility to change the procedure. Precision of both methods is suitable for clinical use. A time advantage using the robot-arm couldn’t be demonstrated in the present study. A significant learning curve was shown, so a reduction in the longer duration on the robot can be expected. Further studies in clinical use are necessary.
CRIS-Team Scopus Importer:2024-11-22